2021
DOI: 10.3233/shti210836
|View full text |Cite
|
Sign up to set email alerts
|

Are Semantic Annotators Able to Extract Relevant Complexity-Related Concepts from Clinical Notes?

Abstract: Clinical decision support systems (CDSSs) implementing cancer clinical practice guidelines (CPGs) have the potential to improve the compliance of decisions made by multidisciplinary tumor boards (MTB) with CPGs. However, guideline-based CDSSs do not cover complex cases and need time for discussion. We propose to learn how to predict complex cancer cases prior to MTBs from breast cancer patient summaries (BCPSs) resuming clinical notes. BCPSs being unstructured natural language textual documents, we implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…We previously used semantic annotators to extract structured data from textual BCPSs [3]. ECMT and SIFR [4] are two annotators that work for the French language.…”
Section: Extraction Of Structured Data From Bcpssmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously used semantic annotators to extract structured data from textual BCPSs [3]. ECMT and SIFR [4] are two annotators that work for the French language.…”
Section: Extraction Of Structured Data From Bcpssmentioning
confidence: 99%
“…As a result, all BCPSs were available in both French and English. As a previous work [3] concluded that the application of all four annotators gave the best set of annotations, including complexity-related concepts, we executed the four annotators, and processed the output of each annotator to generate a semantic representation of a BCPS as two vectors, a vector of UMLS concepts (CUI) extracted by SIFR, cTAKES, and MetaMap. And a second vector containing the labels of the concepts extracted by ECMT (ECMT does not extract UMLS CUIs).…”
Section: Extraction Of Structured Data From Bcpssmentioning
confidence: 99%